Customer Satisfaction Analysis System Using the Customer Satisfaction Index at BSI (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
Bank Syariah Indonesia (BSI)KCP Bengkong,Batam.Did not have an accessible application to measure customer satisfaction ,making it defficult to evaluate service quality and identify areas for improvement This study aimed to design and implement a customer satisfaction analysis system using the Customer Satisfaction Index (CSI) method. The system was developed using the Waterfall model and designed with Unified Modeling Language (UML). Data were collected through questionnaires distributed to 30 respondents with 15 assessment items. The developed application was tested using black-box testing and was successfully implemented. The results showed a CSI value of 99.38, which indicated a “Very Satisfied” category. The system provided an effective tool for measuring customer satisfaction and supporting service quality improvement at BSI KCP Bengkong, Batam.